A Step Forward Toward Controlling Leptospirosis: Comprehensive and Collective Efforts - Mehta, Megha; Patel, Prakash B; Patel, N B; Gharat, Vaibhav; Bansal, R K (National Journal of Community Medicine, 2013)
Introduction: Leptospirosis is a globally important bacterial zoonotic disease occurring in rural areas of South Gujarat. Primary prevention of Leptospirosis is very difficult. This study was planned for early detection and timely referral of cases; increase awareness in high risk population regarding primary prevention and early treatment seeking; and establish and strengthen case suspicion and referral network in the community itself. Methodology: This intervention study was conducted in villages of Surat district with main focus on early recognition of symptoms of Leptospirosis and timely health care seeking. Multipronged approach including meeting with villages, local leader and local health functionaries were used as an intervention. Results: Mass campaign resulted in early health seeking behavior for suspected symptoms which is evident from gross increase in case reporting compare to previous year. These cases were reported early in their clinical course and timely treatment resulted in decreased case fatality rate from 24% in year 2012 to 9.5% in 2013. Conclusion: The comprehensive effort involving every strata of the community from health staff to Sarpanchs/local leaders to local community under one roof has desirable and positive impact on the implementation of leptospirosis control in form of early treatment seeking and timely referral.